Short report: Post-operative wound infections after the gentle caesarean section. (October 2019) - Bronsgeest, Kim; Wolters, Vera E.R.A.; Freeman, Liv M.; te Pas, Arjan B.; Kreijen-Meinesz, Janneke H.; Boers, Kim E.
Abstract: Objectives: Worldwide, the caesarean section (CS) is the most performed type of surgery and numbers are still rising. The gentle CS has become a more common procedure as it allows the parents to experience birth. Early and continuous skin-to-skin contact between the mother and her newborn is pursued. Parents are not separated from their newborns and stay with their child in the operation theatre and recovery room. However, data are limited on the incidence of surgical site infections (SSI) after gentle CS. The aim of our study was to examine the risk of postoperative wound infections after gentle CS. Secondary outcomes included other maternal complications and neonatal outcomes. Study design: In this multicenter prospective cohort study, all women who underwent an elective gentle CS between January 2015 and January 2017 were eligible. Demographics, per procedural data, maternal complications and neonatal outcomes were collected. The follow-up lasted until six weeks post partum. Results: Of the 243 performed CSs, two (0.8%) SSIs occurred; one superficial and one deep wound infection. One patient (0.4%) was readmitted for treatment of endometritis. In total, 20 (8.2%) maternal complications were identified. Median time to skin-to-skin contact was 3 minutes (IQR 2–4.25) with a median neonatal oxygen saturation 10 minutes after birth of 95% (IQR 92–98). Mean gestational age was 274 ± 4.1 days (39 + 1 weeks) and mean neonatal pH was 7.28 (±SD 0.07). All children had Apgar scores >7 at 5 minutes after birth. Neonatal admission occurred in 19 cases (7.8%) and neonatal readmission in 10 cases (4.1%). Conclusion: The gentle CS seems to be a safe procedure for both mother and child and is not associated with an increased risk of surgical site infections or direct suboptimal neonatal outcomes. Therefore, more intensive mother-child interaction during CS is allowed.